2014
DOI: 10.1186/1475-2891-13-110
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine ameliorated fasting-induced fatigue, hunger, and metabolic abnormalities in patients with metabolic syndrome: a randomized controlled study

Abstract: BackgroundThe present study aimed to determine that whether L-carnitine infusion could ameliorate fasting-induced adverse effects and improve outcomes.MethodIn this 7-day, randomized, single-blind, placebo-controlled, pilot study, 15 metabolic syndrome (MetS) patients (11/4 F/M; age 46.9 ± 9.14 years; body mass index [BMI] 28.2 ± 1.8 kg/m2) were in the L-carnitine group (LC) and 15 (10/5 F/M; age 46.8 ± 10.9 years; BMI 27.1 ± 2.3 kg/m2) were in the control group (CT). All participants underwent a 5-day modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 47 publications
5
27
0
2
Order By: Relevance
“…Consistent with this, a previous study has shown decreased fatty acid accumulation in the livers of diabetic mice upon carnitine supplementation [51]. This proposed mechanism of carnitine facilitated fatty acid oxidation has led to multiple clinical trials with mixed results on metabolic parameters including blood glucose and lipid levels [52-54]. …”
Section: Discussionsupporting
confidence: 60%
“…Consistent with this, a previous study has shown decreased fatty acid accumulation in the livers of diabetic mice upon carnitine supplementation [51]. This proposed mechanism of carnitine facilitated fatty acid oxidation has led to multiple clinical trials with mixed results on metabolic parameters including blood glucose and lipid levels [52-54]. …”
Section: Discussionsupporting
confidence: 60%
“…a), which is consistent with previous reports using mouse models fed HFD and irregular diets . The reduction of body weight by L‐carnitine has also been reported in obese patients with metabolic syndrome and polycystic ovary syndrome . Moreover, L‐carnitine improved hyperlipidemia, hyperglycemia, and hyperinsulinemia (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, in a study by Ismail et al ., combined l ‐carnitine and clomiphene citrate significantly improved both ovulation and cumulative pregnancy rates in patients with clomiphene‐resistant PCOS. Taking intravenous l ‐carnitine (4 g/day) among patients with MetS for 7 days resulted in weight loss, improved fasting‐induced hunger and cholesterol abnormalities . Carnitine supplementation in human studies and animal models has indicted an improvement in parameters of glucose homoeostasis, particularly during an insulin‐resistant state .…”
Section: Introductionmentioning
confidence: 99%
“…Taking intravenous L-carnitine (4 g/day) among patients with MetS for 7 days resulted in weight loss, improved fasting-induced hunger and cholesterol abnormalities. 12 Carnitine supplementation in human studies and animal models has indicted an improvement in parameters of glucose homoeostasis, particularly during an insulin-resistant state. 13,14 However, carnitine administration did not affect weight loss outcomes in valproate-treated bipolar patients consuming an energy-restricted and low-fat diet.…”
Section: Introductionmentioning
confidence: 99%